A Photochemical Vapor Generation Method for the Determination of Hg and Pb in Imitation Jewelry by Inductively Coupled Plasma Optical Emission Spectrometry - Fernanda P. Braga; Jefferson Santos de Gois (Chemosensors)
The monitoring of contaminants in imitation jewelry has become important nowadays due to the high amount of products sold worldwide. Due to the complexity of the sample matrix (composed mainly of metals in high concentration), sample analysis can be very challenging. One interesting alternative for this purpose is the use of photochemical vapor generation coupled to inductively coupled plasma optical emission spectrometry (PVG-ICP-OES) due to the ability of separating the analytes from the sample solution prior to analysis; additionally, it is considered an eco-friendly approach if compared to other vapor generation techniques. Thus, this work presents the development and application of a PVG-ICP-OES system for the determination of Hg and Pb in imitation jewelry after sample dissolution in hydrochloric acid. The PVG system was built with two UV lamps (254 nm), a quartz capillary reactor, and a glass gas-liquid separator. Acetic acid concentration and UV exposure time were optimized using a central composite design, as well as the carrier gas flow rate and the radiofrequency (RF) power for the ICP-OES. The optimum conditions were achieved at 30% v/v acetic acid, 60 s reaction time, 0.035 L min−1 carrier gas flow rate, and 1310 W for RF power. The influence of the sample matrix and chemical modifiers were studied, where it was found that the presence of the sample matrix may cause suppression of the analytical signal. The accuracy of the method was evaluated by recovery tests, which ranged from 88 to 102%. The detection limits ranged from 1 to 3 mg g−1, allowing the monitoring of Hg and Pb in imitation jewelry.